Radiological Analysis of Olfactory Fossa Depth: A Tertiary Care Hospital Based Study - Shrestha, Bikash Lal; Karmacharya, Sameer; Shrestha, Krishna Sundar (Birat Journal of Health Sciences, 2019)
Introduction: Computed tomogram (CT) of nose and paranasal sinuses provides the detailed knowledge of depth of olfactory fossa as per Keros’ classification, which is important in endoscopic sinus surgery. Objective: To analyze the types and frequency of depth of olfactory fossa in Nepalese population. Methodology: This was a longitudinal study conducted from 1 May to 30 August 2018. Coronal CT scans of nose and paranasal sinuses were taken for analysis of olfactory fossa depth. The landmarks like infraorbital foramen, point of articulation of medial ethmoidal roof with lateral lamella of cribriform plate (MERP) and lowest point on the cribriform plate (CP) were taken. The lateral lamella of cribriform plate (LLCP) was calculated by subtracting CP height from MERP height (MERP-CP = LLCP). Results: There were total 101 patients included. The distribution of age was 33.72 ± 15.15 years. The keros’ type I was the most common (86.1%). Regarding the olfactory fossa depth, right side was deeper in male whereas in females, the left side was deeper, but overall right side was deeper in 52(51.5%) patients. Conclusions: Type I Keros’ was the most common whereas type III Keros’ was the least common. A deep olfactory fossa is more common on right.